The Influence of Check Point Unit Aviation Security (AVSEC) Security Services on Passenger Satisfaction at Yogyakarta International Airport - Mansur, Heidy Arisanti; Prakosawati, Elisabeth Endang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Licensed aviation security officers, known as Aviation Security, are responsible for managing and providing security services at airports. One of the main roles of Aviation Security (AVSEC) is to ensure the quality of security services at the Yogyakarta International Airport Security Check Point (SCP) for passengers. In research conducted in the November-December 2022 period at YIA Airport, it was found that a number of Avsec officers were still not friendly enough in providing services to consumers. The aim of this research is to understand the impact of the quality of Security Check Point security services by AVSEC officers on the level of passenger satisfaction at Yogyakarta International Airport. Apart from that, this research also aims to assess the extent to which the quality of Security Check Point security services by AVSEC officers influences passenger satisfaction at Yogyakarta International Airport. This research adopted a quantitative approach and was carried out at Yogyakarta International Airport. Respondents in this study consisted of fifty aviation security officers. To collect data, researchers used observation, questionnaires and documentation methods. Data management is carried out through simple linear regression analysis